THE IMPLEMENTATION OF ONLINE MEDIA METHOD IN TEACHING TRANSLATION - hastuti, diyah murti (Manajemen Pendidikan, 2020)
The process of learning and teaching translation still becomes something difficult for teachers and students in Indonesia. Currently the method used by teachers for teaching translation is still traditional method. So that, students feel bored while learning translation because they get the same instruction every time. Thus, it needs to implement a modern method for teaching translation to engage and motivate students in learning translation. The aim of the research is to find out the effective and appropriate method for teaching translation of senior school students. In addition, researcher also wants to know the effectiveness of Online Media method for teaching translation. The research method is descriptive qualitative. The collecting data was conducted by observing the students at Senior School during Translation teaching. This action research was the process of learning and community empowerment. Based on the observation, Indonesia teacher tends to use traditional method for teaching translation. Teaching translation by using online media gives something positive to students. Students become more active after learning with on-line media than traditional method.Teaching approach used by the teacher changed from teacher centered to student centered, the lesson materials were more practical given and learned in the Online Media Features class than in the traditional class. The teaching method in translation improved significantly in the Online Media Features class because all were enhanced with interactive web technology. In addition, in the Online Media Features class the students and teacher engaged in active learning and did problem solving together. Keywords: Translation, Translation teaching method, traditional method, Online media method